QUALITY DEVELOPMENT POLICY MODEL PRIVATE JUNIOR HIGH SCHOOL TEACHER - Muhammad Ali Napiah Lubis; Samrul Bahri Hutabarat; Syafaruddin Syafaruddin; Makmur Syukri (IAIN Padangsidimpuan, 2022)
This research focuses on examining the policy model for developing the quality of private junior high school teachers in the Pandan District. This research study used the field method (field research). The results of this study are that in order to develop the quality of teachers, the leaders of private junior high schools in Pandan District need to: (1) Create, compile and formulate the vision, mission, and goals of the institution, especially the development of teacher quality; (2) Building commitments that are worth worship; (3) Build attitude and discipline; (4) Changing mindsets and building positive teacher character. Teacher quality improvement continues to develop dynamically. Participation in improving the quality of teachers must continue to be considered and continuously guarded by all parties.